Znaczenie efektywności ekonomicznej w procesach decyzyjnych przedsiębiorstw - Wrzosek, Stefan (The Signification of the Economic Efficiency in the Companies Decisions Processing, 2005)
Aiming to high efficiency in firms is very complex especially because of necessity of submitting current decisions, which have actual, measurable effects, to less convincing strategic decisions. This often makes necessary to resign from very probable and measurable short term effects, to create conditions to achieve uncertain long time efficiency. An important way of integrating of current and strategic decisions is use the enterprise value criterion.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 459-462